Neural Mechanisms of Motion Detection, Integration, and Segregation: From Biology to Artificial Image Processing Systems. (10th November 2010) - Bouecke Bouecke, Jan D. Jan D.; Tlapale Tlapale, Emilien Emilien; Kornprobst Kornprobst, Pierre Pierre; Neumann Neumann, Heiko Heiko
Abstract : Object motion can be measured locally by neurons at different stages of the visual hierarchy. Depending on the size of their receptive field apertures they measure either localized or more global configurationally spatiotemporal information. In the visual cortex information processing is based on the mutual interaction of neuronal activities at different levels of representation and scales. Here, we utilize such principles and propose a framework for modelling neural computational mechanisms of motion in primates using biologically inspired principles. In particular, we investigate motion detection and integration in cortical areas V1 and MT utilizing feedforward and modulating feedback processing and the automatic gain control through center-surround interaction and activity normalization. We demonstrate that the model framework is capable of reproducing challenging data from experimental investigations in psychophysics and physiology. Furthermore, the model is also demonstrated to successfully deal with realistic image sequences from benchmark databases and technical applications.